Image-based sexual abuse and bystander intervention: a mixed methods study of attitudes, barriers and facilitators - Flynn, Asher (Palgrave studies in cybercrime and cybersecurity, 2025)
" The Pivot explores bystander intervention and image-based sexual abuse. It fills a critical gap in the market on a significant and contemporary legal, social, public health, and criminal justice issue. It is timely in light of a number of recent high-profile instances of image-based sexual abuse perpetration, including those involving the non-consensual digital altering and sharing of sexual imagery - sexualised "deepfakes" created with AI, digital tools or software - of celebrities (e.g. Taylor Swift) and young women. This book draws upon the first mixed methods study of its kind globally and makes a substantial contribution to the conceptualisation of image-based sexual abuse and bystander intervention; an issue that has not yet been explored in detail. Drawing on criminology, gender studies, psychology, and law, it provides new theoretical and practical insights of particular relevance to practitioners, stakeholders, and government and non-government organisations on how bystander intervention can be an untapped prevention resource." --